A note on the asymmetric part of an outranking relation. (21st November 2014) - Bouyssou, Denis; Pirlot, Marc
Abstract This paper discusses the properties of the asymmetric part of an outranking relation built as in ELECTRE. Such relations have been used in the pseudodisjunctive version of ELECTRE TRI‐B. We show that they have properties that are somewhat different from that of outranking relations. Indeed, contrary to outranking relations, they allow to have at the same time veto and bonus effects. We suggest that this explains the difficulty in analyzing the properties of the pseudodisjunctive version of ELECTRE TRI‐B and the complexity of the elicitation methods of its parameters. We present conditions that characterize such relations.